Merritt's neurology - Louis, Elan D.; Mayer, Stephan A.; Rowland, Lewis P. (Wolters Kluwer, 2016)
Completely updated and in brilliant full color, Merritt's Neurology, 13th Edition, remains your reference of choice for outstanding guidance on neurologic protocols, treatment guidelines, clinical pathways, therapeutic recommendations, and imaging. Greatly reorganized for ease of use, the 13th Edition features more than 30 new chapters that keep will you up to date with every aspect of your field. Now for the first time, you'll find dozens of video clips online that demonstrate the clinical signs and symptoms of neurologic disorders.